Interleukin 4 gene polymorphism (−589C/T) and the risk of asthma: a meta-analysis and met-regression based on 55 studies - Kousha, Ahmad; Mahdavi Gorabi, Armita; Forouzesh, Mehdi; Hosseini, Mojgan; Alexander, Markov; Imani, Danyal; Razi, Bahman; Mousavi, Mohammad Javad; Aslani, Saeed; Mikaeili, Haleh (BMC immunology, 2020)
Numerous investigations have previously evaluated the association of interleukin (IL) 4 gene polymorphisms and the risk of asthma, conferring inconsistent results. To resolve the incongruent outcomes yielded from different single studies, we conducted the most up-to-date meta-analysis of IL4 gene -589C/T (rs2243250) polymorphism and susceptibility to asthma. A systematic literature search was performed in ISI web of science, Scopus, Medline/PubMed databases prior to September 2020, and the pooled odds ratio (OR) and their corresponding 95% CI were calculated to determine the association strength. Literature search led to retrieving of 49 publications (55 case-control studies) containing 9572 cases and 9881 controls. It was revealed that IL4 gene -589C/T polymorphism increased the risk of asthma across all genetic models, including dominant model (OR = 1.22), recessive model (OR = 1.17), allelic model (OR = 1.21), and TT vs. CC model (OR = 1.34), but not the CT vs. TT model. The subgroup analysis by age indicated that IL4 gene -589C/T polymorphism was significantly associated with asthma risk in both pediatrics and adults. Additionally, the subgroup analysis by ethnicity revealed significant association in Asian, American, and Europeans. Finally, subgroup analysis by East Asian and non-East Asian populations indicated significant associations. The current meta-analysis revealed that IL4 gene -589C/T polymorphism was a susceptibility risk in both pediatrics and adults in the whole and different ethnic groups.